MATEC Web of Conferences - Ivanova; Kobenko; Kulkova; Riabova (EDP Sciences, 2018)
The article presents the examples of comparing chemical terms in the Chinese and Russian languages and the results of two experiments conducted with Chinese and Russian students. The first part of the work deals with a comparison of the one-component chemical element names from the periodic table. Then, it continues with dividing different chemical terms in Chinese into several groups: two-component, three-component, four-component, multicomponent group and comparing them with its analogical terms in Russian to analyze the main difficulties in understanding these terms in both languages. The second part of the work presents the main difficulties, revealed during two experiments, conducted with Chinese and Russian students. The students were given texts in their mother tongues with a chemical context, which they wrote and read noting the time. At the end of the work, all the advantages and complexities revealed in the results of the first and second parts of the work were calculated. Similar language comparisons are becoming more relevant in the last few years, for they contribute to development of methods of analyzing languages and discovering new and improved approaches to the study and use of languages.